Kadar Fenolat dan Flavonoid Total serta Kapasitas Antioksidan Ekstrak Etanol dan Fraksi Jahe Merah (Zingiber officinale var. Rubrum) - Dwi Koko Pratoko; Firdha Aprillia Wardhani; Nia Kristiningrum; Fifteen Aprila Fajrin; Dian Agung Pangaribowo (Al-Kimia, 2018)
Determination of total phenolic, total flavonoid, and antioxidant capacity of ethanolic extract and fractions from red ginger (Zingiber officinale var. Rubrum) has been done. Red gingers contain the highest oleoresins among other ginger varieties. Oleoresins are component that had the most responsibility for pharmacological effect of red ginger, one of them is as antioxidant. Phenolic and flavonoid are highly contributing to the antioxidant effect of red ginger. The aim of this research is to determine the antioxidant capacity of extract and fractions of red ginger, and to investigate the correlation between antioxidant capacity with both total phenolic and total flavonoid. Ethanolic extracts are fractinationed with n-hexane, chloroform, ethyl acetate, n-butanol, and methanol solvent. Antioxidant capacity, total phenolic, and total flavonoid of all the samples are measured. Highest antioxidant capacity, total phenolic, and total flavonoid obtained from ethyl acetate fraction with TEAC 2143.9 ± 0.9 µmol/g (CUPRAC) and 4526.4 ± 3.0 (DPPH), GAE 229.9 ± 1.3 mg/g, and QE 46,6 ± 1,8 mg/g. One way ANOVA and post hoc analysis show significant result with p value <0,01. Pearson correlation shows high positive correlation. Determination of total phenolic, total flavonoid, antioxidant capacity from ethanolic extract and fractions of red ginger (Zingiber officinale var. Rubrum) has been done.Red ginger contain the highest oleoresins among other ginger varieties. Oleoresins are component that had the most responsibility for pharmacological effect of red ginger, one of them is as antioxidant. Phenolic and flavonoid are highly contribute to the antioxidant effect of red ginger. The aim of this research is to determine the antioxidant capacity of extract and fractions of red ginger, and to investigate the correlation between antioxidant capacity with both total phenolic and total flavonoid. Ethanolic extracts are fractinationed with n-hexane, chloroform, ethyl acetate, n-butanol, and methanol solvent. Antioxidant capacity, total phenolic, and total flavonoid of all the samples are measured. Highest antioxidant capacity, total phenolic, and total flavonoid obtained from ethyl acetate fraction with TEAC 2143,893 ± 0,890 µmol/g, GAE 229,878 ± 1,330 mg/g, and QE 46,564 ± 1,804 mg/g. One way ANOVA and post hoc analysis show significant result with p value <0,01. Pearson correlation shows high positive correlation.